Thromboelastography-Guided Therapy Enhances Patient Blood Management in Cirrhotic Patients: A Meta-analysis Based on Randomized Controlled Trials - Hartmann, Jan; Dias, Joao D.; Pivalizza, Evan G.; Garcia-Tsao, Guadalupe (Seminars in Thrombosis and Hemostasis, 2022)
Patients with cirrhosis often have abnormal hemostasis, with increased risk of hemorrhage and thrombosis. Thromboelastography provides a rapid assessment of the coagulation status and can guide product transfusions in adult patients with cirrhosis. This study aimed to determine whether the use of thromboelastography in adult patients with cirrhosis decreases blood product use and impacts adverse events or mortality compared with standard practice. A registered (PROSPERO CRD42020192458) systematic review and meta-analysis was conducted for randomized controlled trials (RCTs) comparing thromboelastography-guided hemostatic management versus standard practice (control). Co-primary outcomes were the number of transfused platelet units and fresh frozen plasma (FFP) units. Secondary outcomes were mortality, adverse events, utilization of individual blood products, blood loss or excessive bleeding events, hospital/intensive care unit stay, and liver transplant/intervention outcomes. The search identified 260 articles, with five RCTs included in the meta-analysis. Platelet use was five times lower with thromboelastography versus the control, with a relative risk of 0.17 (95% confidence interval [CI]: [0.03–0.90]; p = 0.04), but FFP use did not differ significantly. Thromboelastography was associated with less blood product (p < 0.001), FFP + platelets (p < 0.001), and cryoprecipitate (p < 0.001) use. No differences were reported in bleeding rates or longer term mortality between groups, with the thromboelastography group having lower mortality at 7 days versus the control (relative risk [95% CI] = 0.52 [0.30–0.91]; p = 0.02). Thromboelastography-guided therapy in patients with cirrhosis enhances patient blood management by reducing use of blood products without increasing complications.
Keywords: thromboelastography; cirrhosis; blood products; patient blood management